ä½¿ç”¨ä»»åŠ¡åž‹æ•™å¦æ³•æé«˜ä»¥é©¬å†…åˆ©äºŒæ ¡åˆä¸ä¸€å¹´çº§å¦ç”Ÿçš„ æ±‰è¯å£è¯èƒ½åŠ› - Trihartati, .; ., Ina; ., Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
æ‘˜è¦: å£è¯æ˜¯å£å¤´äº¤é™…ä½¿ç”¨çš„è¯è¨€ï¼Œåœ¨å¯¹å¤–æ±‰è¯åˆ†æŠ€èƒ½çš„æ•™å¦æ¨¡å¼ä¸å£è¯è¯¾æ˜¯éžå¸¸é‡è¦çš„ä¸€ä¸ªè¯¾ç¨‹ã€‚ä½†æ˜¯ç¬”è€…åœ¨ä»¥é©¬å†…åˆ©äºŒæ ¡åˆä¸ä¸€å¹´çº§Cçè¿›è¡Œ è§‚å¯ŸåŽäº†è§£åˆ°å¦ç”Ÿéš¾ä»¥è¿›è¡Œä¼šè¯æ´»åŠ¨ï¼Œå¦ç”Ÿæ— æ³•ç”¨æ±‰è¯è·Ÿåˆ«äººè¯´å‡ºè‡ªå·±æœ€ ç®€å•çš„ä¿¡æ¯æˆ–æ€æƒ³ã€‚ç¬”è€…ä½¿ç”¨ä»»åŠ¡åž‹æ•™å¦æ³•å¯¹è¯¥æ ¡ä¸€å¹´çº§Cççš„å¦ç”Ÿè¿›è¡Œäº†ç ”ç©¶ï¼Œä¸ºçš„æ˜¯äº†è§£ä»»åŠ¡åž‹æ•™å¦æ³•æ˜¯å¦èƒ½å¸®åŠ©è¯¥æ ¡çš„å¦ç”Ÿæé«˜æ±‰è¯å£è¯èƒ½åŠ›ã€‚ç»“æžœè¡¨æ˜Žæ¤æ•™å¦æ³•ç¡®å®žèƒ½å¤Ÿæé«˜å¦ç”Ÿçš„å£è¯èƒ½åŠ›ã€‚å‰æµ‹æ—¶ï¼Œå‘éŸ³ä¸åŠæ ¼çš„ å¦ç”Ÿæœ‰70%ï¼Œè¯æ³•40%ï¼Œè¯æ±‡35%ï¼Œæµåˆ©ç¨‹åº¦65%ï¼Œç†è§£èƒ½åŠ›65%ï¼›è€Œ åŽæµ‹çš„æ—¶å€™å‘éŸ³ä¸åŠæ ¼çš„åªæœ‰15%ï¼Œè¯æ³•15%ï¼Œè¯æ±‡5%ï¼Œæµåˆ©ç¨‹åº¦5%ï¼Œç†è§£èƒ½åŠ›15%ã€‚ å…³é”®è¯ : ä»»åŠ¡ï¼Œä»»åŠ¡åž‹æ•™å¦æ³•ï¼Œå£è¯ Abstract: Oral communication is the using of verbal voice. Foreign Language Skills in sub Oral communication teaching is a very important lesson. But, when the author did an observation at SMP (Junior High School) Emanuel two, found that the students feel difficult to do conversation, students are unable to express theirÂ  simplest information with other people in Chinese.Author used Task - based Approach (TBLT) to Grade C of the first level of Junior High School Students in order to know whether the task-based approach can help students to improve their Chinese speaking skill. The results indicate that this teaching method can indeed improve students' speaking skills. The pre-test showed, pronunciation fail of students is 70% of grammar 40% vocabulary 35% fluency 65% comprehension 65%. But, post-test only 15% of pronunciation fail, grammar 15%, vocabulary 5% , 5% fluency, comprehension of 15%. Keys WordsÂ Â  : Task, Task-Based Language Teaching (TBLT) , Speaking